2020
DOI: 10.1016/j.scriptamat.2020.07.053
|View full text |Cite
|
Sign up to set email alerts
|

Decoupled versus coupled growth dynamics of an irregular eutectic alloy

Abstract: We present an experimental study of irregular growth patterns observed in real time during thin-sample directional solidification of a faceted/nonfaceted eutectic alloy, namely, the transparent 2-amino-2-methyl-1,3-propanediol (AMPD)-succinonitrile (SCN) system. The body-centered cubic SCN crystals are nonfaceted, while monoclinic AMPD crystals grow as faceted needles. At low velocities (<0.3 µms -1 ), a decoupled growth regime is observed, during which the tip of the AMPD crystals grows ahead of the SCN-liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…We used a model organic transparent alloy system and in-situ observations to investigate the growth dynamics of irregular eutectic alloys. V-ramp imposed by the RDS experiments enabled us to further investigate the various microstructures obtained at different velocities during DS experiments [3] at the same solidification front. Observing all the three previously reported microstructures at the same solidification front confirms that for a given alloy composition, both the microstructure and the growth dynamics, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a model organic transparent alloy system and in-situ observations to investigate the growth dynamics of irregular eutectic alloys. V-ramp imposed by the RDS experiments enabled us to further investigate the various microstructures obtained at different velocities during DS experiments [3] at the same solidification front. Observing all the three previously reported microstructures at the same solidification front confirms that for a given alloy composition, both the microstructure and the growth dynamics, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their practical importance, scientific studies on irregular eutectics remain essentially descriptive, and the simultaneous growth of faceted and nonfaceted crystals in an irregular eutectic alloy has been rarely addressed with the aim of highlighting the solidification processes that would not be specific to the chemistry of the alloy. In a recent paper [3], we showed that a faceted/nonfaceted transparent alloy, i.e. Amino-methyl-propanediol/Succinonitrile (AMPD-SCN) at near-eutectic concentration, can be used as an experimental model system for exploring the growth dynamics of irregular-eutectic microstructures in situ.…”
mentioning
confidence: 99%
“…Bu nedenlerden ötürü, Mikroyapı Evrim Laboratuvarında (MEL), katılaşma dinamiklerini gerçek zamanlı incelemek için optik mikroskop kullanılmıştır. Bu yöntem halihazırda çoğunluğu Amerika ve Avrupa'da bulunan birçok üniversitede ve araştırma merkezinde kullanılmaktadır [6,7,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Bu yöntemin yaygın olarak kullanılma sebepleri ise (i) Optik mikroskop ve katılaşma sisteminin diğer yöntemlerden çok daha ucuz ve kolay erişilebilir olması, (ii) Numune eninin X-ışını nanotomografisine göre onlarca kat daha büyük olması ve böylelikle istatiksel olarak geçerli gözlemlerin ve ölçümlerin yapılabilmesi (iii) Elde edilen çözünürlüğün X-ışını mikro-tomografiden çok daha iyi ve nanotomografi seviyelerinde olması ve (iv) Hem organik hem de metalik numunelerin incelebilmesidir.…”
Section: Introductionunclassified